Calculation and experimental evaluation of bogie frame and intermediate frame life of an eight-axle diesel locomotive - S. V. Chunin; A. S. Gasyuk; M. V. Timakov; D. M. Fazliakhmetov; E. V. Muravlev; O. A. Lobachev (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Long-term locomotive operation and safety considerations require new approaches to extending the life of its basic components operating under variable loads.Materials and methods. The authors conducted bench life tests of frames under cyclic loading with vertical and horizontal transverse forces and calculated the bogie frame and intermediate frame life for the most stressed areas of their structures, where local fatigue damage can accumulate under cyclic loading leading to fatigue caused destruction. The calculation uses the results of bench fatigue tests.Results. The research shows that the presented frames comply with GOST R 55513–2013 in terms of minimum reserve strength coefficient for fatigue resistance. The researchers proposed a methodology for estimating the residual life of bogie frames and intermediate frames.Discussion and conclusion. The research indicates that the estimated safe service life of bogie frames and intermediate frames of an eight-axle diesel locomotive does not exceed 56 years from the date of construction. The expiry of this period allows for a repeat research and development work to determine the residual life of its basic parts. The above test methodology could be applied to assess the residual life of bogie frames and intermediate frames whose structure has localised zones of fatigue damage appearance and accumulation from cyclic loading, which may cause fatigue destruction.